Tradisi Toron Etnis Madura: Memahami pertautan agama, budaya, dan etos bisnis - Muhammad Djakfar (el Harakah: Jurnal Budaya Islam, 2012)
Toron or back to the village has been performed as a tradition among the Madurese with various reasons. In understanding the toron tradition which has been a lulture of its own, there is a question whether there are relationships between religious values, culture, and business ethics among the Madurese. This study uses qualitative approach and phenomenological method in order to be able to understand deeper on what the relationship among those three aspects, which can be apprehended from the toron tradition. The data were collected by using observations, in-depth interview, and documentation. The results show that among the students of Islamic boarding schools, the motive of doing toron in commemorating the Prophet’s birthday, is to honour the Prophet, and such celebration is just like a haul for the parents. It is expected that they will receive blessings and help from the Prophet. For those non learners of such boarding schools, it is just like a way (tawassul) to expiate a sin with an expectation to receive blessing from the Prophet. Due to that reason of commemoration, we can understand that there are relationships between religion, culture, and business ethics among the Madurese. Toron atau kembali ke desa telah tampil sebagai tradisi orang Madura dengan berbagai alasan. Dalam memahami tradisi toron yang telah menjadi budaya tersendiri, ada pertanyaan apakah ada hubungan antara nilai agama, budaya, dan etika bisnis di kalangan orang Madura. Penelitian ini menggunakan pendekatan kualitatif dan metode fenomenologis untuk dapat memahami lebih dalam tentang hubungan antara ketiga aspek tersebut, yang dapat ditangkap dari tradisi toron. Data dikumpulkan dengan menggunakan observasi, wawancara mendalam, dan dokumentasi. Hasilnya menunjukkan bahwa di kalangan siswa pesantren, motif melakukan toron dalam memperingati ulang tahun Nabi, adalah untuk menghormati Nabi, dan perayaan semacam itu sama seperti tangkapan untuk orang tua. Diharapkan mereka akan menerima berkah dan pertolongan dari Nabi. Bagi mereka yang bukan pelajar sekolah pesantren seperti itu, sama seperti cara (tawassul) untuk meredakan dosa dengan harapan untuk menerima berkat dari Nabi. Karena alasan peringatan tersebut, kita bisa mengerti bahwa ada hubungan antara agama, budaya, dan etika bisnis di kalangan orang Madura.